Firing Behavior of the Clay Fraction of a Natural Kaolinitic Clay: Are They Different? - Vieira,Carlos Maurício Fontes (2019)
A comparative investigation on the firing behavior of a natural kaolinitic clay from Campos dos Goytacazes, Brazil, and its specific clay fraction was performed. The clay fraction, equivalent diameter less than 2 µm, was separated from the precursor clay by a sedimentation method. Chemical analysis, X-ray diffraction (XRD) and scanning electron microscopy were used to characterize the unfired materials. Thermoanalysis and dilatometry were applied to follow the structural transformations. The firing behavior was studied by water absorption and XRD of samples fired in the temperature range from 400 to 1100°C. Differences were found between the natural kaolinitic clay and its clay fraction. The absence of quartz and smaller particles of the clay fraction result in a comparatively lower temperature for structural consolidation associated with reduced open porosity. This can be attributed to solid state sintering alone, in contrast to a higher temperature liquid phase sintering needed for complete consolidation of the natural kaolinitic clay.